Modeling the effect of enzyme replacement therapy on life-threatening complications in patients with Fabry disease - V. I. Ignatyeva (Фармакоэкономика, 2019)
Fabry disease (FD) is a severe lysosome storage disease caused by congenital deficiency of the enzyme α-galactosidase A and characterized by the risk of renal failure combined with cardiovascular and CNS complications. According to the currently available information, the early start of enzyme replacement therapy (ERT) leads to a significant improvement in patient’s condition.The aim of the study is to assess whether the timely ERT prevents severe FD complications and to calculate the number of prevented cases as depending on the time of ERT start.Materials and methods. The proposed model is based on the published results on patients with FD, receiving agalsidase alpha as ERT (no data for agalsidase beta was found). The expected number of cases with life-threatening complications was calculated for different starting timepoints and durations of the ERT.Results. In patients with FD, continuous ERT during five years reduces the number of serious cardiovascular and renal complications by 25%. An early start of ERT makes it possible to additionally (as compared with a late start) prevent the complications in more than 20% of cases.Conclusion. The early initiation of RPT in patients with FD can significantly reduce the occurrence of severe lifethreatening complications, increase the patients’ survival and improve their quality of life.